Desain Kebijakan City Branding Daerah : (Studi di Kabupaten Blitar, Provinsi Jawa Timur, Indonesia) - Muhammad Lukman Hakim (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
This research focuses on the design of city branding policies in Blitar Regency, East Java Province, Indonesia. Each region is responsible for enhancing its image through promotion and branding as a strategy to attract public and tourist attention. Blitar Regency proves that city branding can have a positive impact on the tourism sector, regional sustainability, and the welfare of its residents. The rebranding effort of tourism with the tagline